2020
DOI: 10.3390/vaccines8010100
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of A20 Expression Increases the Immune Response and Apoptosis and Reduces Virus Production in Cells Infected by the Human Respiratory Syncytial Virus

Abstract: Human respiratory syncytial virus (HRSV) causes severe lower respiratory tract infections in infants, the elderly, and immunocompromised adults. Regulation of the immune response against HRSV is crucial to limiting virus replication and immunopathology. The A20/TNFAIP3 protein is a negative regulator of nuclear factor kappa B (NF-κB) and interferon regulatory factors 3/7 (IRF3/7), which are key transcription factors involved in the inflammatory/antiviral response of epithelial cells to virus infection. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
4
11
0
Order By: Relevance
“…ICAM1 and VCAM1 could receive signals from both MAPK and NF-kB pathways for expression ( Taniguchi and Karin, 2018 ), and contribute to neuron adhesion, stability of extracellular matrix, and permeability of brain barriers. TNFAIP3 (A20) is involved in negative regulation of inflammatory response and apoptosis, and heterozygosity of this gene causes an exacerbated cognitive impairment under inflammatory conditions ( Daems et al, 2020 ; Martín-Vicente et al, 2020 ). The primary function of CCL2 and CXCL10 is chemokines for monocytes and macrophages, but also could indirectly cause neuronal dysfunction through the recruited immune cells ( Lehmann et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…ICAM1 and VCAM1 could receive signals from both MAPK and NF-kB pathways for expression ( Taniguchi and Karin, 2018 ), and contribute to neuron adhesion, stability of extracellular matrix, and permeability of brain barriers. TNFAIP3 (A20) is involved in negative regulation of inflammatory response and apoptosis, and heterozygosity of this gene causes an exacerbated cognitive impairment under inflammatory conditions ( Daems et al, 2020 ; Martín-Vicente et al, 2020 ). The primary function of CCL2 and CXCL10 is chemokines for monocytes and macrophages, but also could indirectly cause neuronal dysfunction through the recruited immune cells ( Lehmann et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In later stages of infection, this improved protection may be associated with suppression of CCL2 expression and modulation of pulmonary cytotoxic T cell [ 79 ]. A study on RSV-infected cells showed that down-regulation of A20 can increase apoptosis and induce an innate immune response in infected epithelial cells [ 80 ]. Zinc exerts an inhibitory effect on the activation of NF-kB by inducing the A20.…”
Section: Resultsmentioning
confidence: 99%
“…Given that circTNFAIP3 is the most significantly dysregulated among the seven validated circRNAs ( Fig. 2A and E ), and its homologous protein TNFAIP3, encoded by the linear transcript of TNFAIP3 gene, plays an important role in inflammation, immunity, and virus infection ( 38 40 ), we therefore wondered if the circular transcript of TNFAIP3 would also be involved in virus infection and selected it for further exploration. Mapping analysis showed that circTNFAIP3 (ssc_circ_0025549, chr1, 29837503 to 29837812) derived from the TNFAIP3 gene is located on chromosome 1 in pigs, according to the ensemble database ( http://ensembl.org ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%